Flexible programme for working adults - The, Star (The Star, 2014)
The degree of Doctor of Business Administration (DBA) research doctorate in business administration that is equivalent to a PhD in Business Administration. Yap Boon Hup said "The academic staff members are supportive. I am happy with my choice to join AeU as a DBA student."